Civil and Military Rules in Indonesia (JPPUMA: Jurnal Ilmu Pemerintahan dan Sosial Politik UMA (Journal of Governance and Political Social UMA), 2021)
Civil and military relations in Indonesia actually have their own rules. If we examine history, we will find phenomena about the relationship between civilian and military power towards the process of social and political change in Indonesia. This paper aims to identify the rules of civil and military play in Indonesia in particular wanting to track civil and military power relations. This study tries to illustrate how the rules of the game between civilians and the military in Indonesia. This paper uses descriptive qualitative methods with data collection techniques by interview and literature study. This paper shows that civilians and the military have their respective duties in carrying out the mandate of the state, these two positions should not interfere with each other. After the reform of civil and military relations, it looks good. One of the agendas is against the Indonesian Armed Forces Dual Function (ABRI) but today, the issue of ABRI's Dual Function has been transformed into a Military Dual Function, ahead of the 2019 General Election (Election) this issue re-emerges so that it is considered political and becomes part of the project's representation of political interests.